Acute Carpal Tunnel Syndrome After Canine Bite. (December 2017) - Brown, Bryan D.; Roth, Travis S.; Gasner, Kurt A.
Abstract : Acute carpal tunnel syndrome (ACTS) from an infected source is rare because most cases result from trauma. There are cases of ACTS occurring after feline bites, but none in the reported literature after canine bites. The following is a case report of a 58-year-old woman who presented to the emergency department with progressive median nerve symptoms after a canine bite. In the operating room, a significant mass effect was found within the contents of the carpal tunnel secondary to an abundance of purulence. The patient was treated urgently with irrigation and débridement of the wrist with an extended open carpal tunnel release and flexor tenosynovectomy and discharged with peripheral venous access for long-term antibiotics. At 1-month follow-up, the healed wound showed no signs of infection. A mild sensory deficit remained in the median nerve distribution.